Concurrent validity and reliability of photoelectric and accelerometer technology for calculating vertical jump height in female athletes - Perrotta, A. S.; Day, B. D.; Wafai, I.; Oates, R. P.; Peterson, M. L.; Scott, A. J.; Barker, R. C.; Garedakis, A. B.; Seaborn, K. A. (Sports Engineering, 2023)
The unremitting development of portable vertical jump equipment emphasizes the need for continual examination of its validity and reliability. Equal representation between sexes should be endorsed in this process to improve precision and application. This study aimed to examine the concurrent validity and reliability of the Exsurgo g-Flight™ photoelectric boxes and the Output Sports V2™ accelerometer for calculating vertical jump height when compared to a dual force plate system (Hawkin Dynamics Force Plate, ME, USA). Twenty (n = 20) female soccer players performed three counter movement jumps on two different sessions for a total of 120 jumps. Comparisons between the criterion method and secondary measures were performed using Bland-Altman plots and were independently examined using a paired samples t-test. Reliability in instrument error was determined by comparing the residuals of each secondary measure over two assessments. Bland-Altman plots revealed = 5.0% of residuals for the accelerometer and photoelectric devices fell outside the limits of agreement. The accelerometer revealed a mean bias (95% CI) of 0.30 ± 0.33 cm, while the photoelectric device demonstrated a negative bias of -1.64 ± 0.45 cm. Mean (± SD) comparisons revealed an overestimation in jump height with the photoelectric device (1.6 ± 4.0 cm, p < 0.0001) and insignificant differences with the accelerometer (0.30 ± 3.7 cm, p > 0.05). Mean differences in residuals between testing dates for secondary measures were insignificant (p = 0.23). Both the photoelectric and accelerometer instruments displayed high reliability, but differences in the accuracy between devices were observed.